«ΑΓΟΡΑ ΤΟΥΡΚΟΥ ΣΚΛΑΒΟΥ» ΣΤΗ ΣΙΦΝΟ (17ΟΣ ΑΙ.). Η ΑΠΟΣΠΑΣΜΑΤΙΚΟΤΗΤΑ ΤΩΝ ΠΗΓΩΝ - ΣΠΗΛΙΩΤΟΠΟΥΛΟΥ, ΜΑΡΙΑ (Μνήμων, 2005)
Maria Spiliotopoulou, "The purchase of a Turkish slave" in Sifnos (XVII c.) A document concerning the investment on a Turkish slave in Sifnos, during the XVII c, and the example of the enterprises of the GreekOrthodox Archbishop of Sifnos, constitute the starting-point for an attempt to discern the forms of collaboration between the high GreekOrthodox clergy and the corsairs in the Aegean, as also the contribution of the slave commerce in the formation of big fortunes and the accumumulation of ready money. Documents deposited in the Archive of the Diocese of Santorini, from where the Archbishop originated, are used in order to understand the meaning of such a document and to study the facts despite the disjointed nature of the historical data.